واقع ومتطلبات إعادة هيكلة وتأهيل تنافسية شعبة تحويل الحبوب ومشتقاتها في الجزائر.: The Reality and Requirements for Restructuring and Rehabilitating the Competitiveness of the Cereals and their Derivative Branch in Algeria. - فريد حدادة; عماد سعادي (Journal of North African Economies, 2025)
This study aims to highlight the role of the new direction of the Algerian authorities to advance the food industry sector in general and the Cereals and their derivative branch in particular, in order to improve and raise the competitiveness of this branch in the local and international markets. This will create greater added value to the product and increase its competitiveness; The Algerian authorities are working with all parties concerned with this branch to restructure and rehabilitate the Cereals and their derivative branch 8 On the other hand, it is matched by a low level of yield of grain production estimated at: 18.8 quintals/ha, which forces Algeria to import between 74 to 80% of its grain needs, in addition to the difficulties of supplying raw materials (cereals), resulting from the quota system applied by Party (OAIC), it only provides between 35-40% of the needs of the transferred institutions.